2008
DOI: 10.1177/0731684408090844
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Moisture Effects in a Particulate Interlayered Composite: Mode I Data Reduction and Toughness

Abstract: A study was conducted to determine the mode I toughness of T800H/3900-2 graphite/ epoxy under a range of environments that are typical of aircraft and spacecraft operating conditions. Double cantilever beam tests were performed on both dry and moisture-saturated specimens at temperatures of À43, 21, and 988C, and on dry specimens only at 1258C. Under certain conditions, nonlinear behavior and permanent deformations were observed. Thus, a sub-study was performed to choose a data reduction method that could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In the international literature, plenty of analytical research devoted to Mode I investigation can be found. Multiple data reduction methods based on Linear Elastic Fracture Mechanics (LEFM) have been developed and can be categorized as: the compliance calibration methods based on experiments defining the relationship of the compliance versus the crack length [28,29]; the compliance calibration methods derived from the classical and modified beam theory [30,31]; an approach determining the energy release rate from the ratio of change in strain energy to the change in crack area [32]; and a reduction method using the J-integral as a fracture parameter [33]. The expressions for critical energy release rate used in this work are based on the work of Williams [30,34] and Hashemi et al [31] leading to Equation (12).…”
Section: Analytical Solution For the Mode I Dcb Testmentioning
confidence: 99%
“…In the international literature, plenty of analytical research devoted to Mode I investigation can be found. Multiple data reduction methods based on Linear Elastic Fracture Mechanics (LEFM) have been developed and can be categorized as: the compliance calibration methods based on experiments defining the relationship of the compliance versus the crack length [28,29]; the compliance calibration methods derived from the classical and modified beam theory [30,31]; an approach determining the energy release rate from the ratio of change in strain energy to the change in crack area [32]; and a reduction method using the J-integral as a fracture parameter [33]. The expressions for critical energy release rate used in this work are based on the work of Williams [30,34] and Hashemi et al [31] leading to Equation (12).…”
Section: Analytical Solution For the Mode I Dcb Testmentioning
confidence: 99%
“…A lot of research has been effectuated on the analytical calculation of the mode I fracture toughness G Ic . Multiple data reduction methods based on Linear Elastic Fracture Mechanics (LEFM) have been developed and can be categorized as: the compliance calibration methods based on experiments defining the relationship of the compliance versus the crack length [28,29,30]; the compliance calibration methods derived from the classical and modified beam theory [31,32,33]; an approach determining the energy release rate from the ratio of change in strain energy to the change in crack area [33,34] and finally a reduction method using the Jintegral as a fracture parameter [3,35]. The expressions for G Ic used in this work are based on the work of Williams [31,36] and Hashemi et al [33] leading to the equations below.…”
Section: Analytical Solution For the Mode I Dcb Testmentioning
confidence: 99%
“…Correspondingly needs to be characterizing the fracture toughness over environmental conditions. This behaviour has been interrelated to the effect of moisture on matrix ductility, an amount of matrix deformation and the size of the plastic zone around the crack tip that occurs during fracture [4]. For fiber-reinforced composite materials, the interlaminar and/or intralaminar interface will have a great effect on their fracture mechanisms.…”
Section: Introductionmentioning
confidence: 99%